DEVELOPMENT OF COOPERATIVE AND WORK-INTEGRATED EDUCATION OF ART DESIGN MAJOR IN HIGHER VOCATIONAL COLLEGES UNDER HENAN PROVINCE - Chen, Yang; Chinatangkul, Chuanchom; Chaisirithanya, Kamolmal (วารสารวิจัยธรรมศึกษา, 2025)
The objectives of this research were: (1) to explore the components of Cooperative and Work-Integrated Education (CWIE) of Art Design Major in Higher Vocational Colleges under Henan Province; and (2) to develop guidelines for development of Cooperative and Work-Integrated Education of Art Design Major in Higher Vocational Colleges under Henan Province. The research was a mixed methodology research, which consisted of quantitative research and qualitative research. The population of the research included 1,482 professional teachers and educational administrators of art and design majors from 39 higher vocational colleges in Henan Province, the People's Republic of China. The sample of 306 professional teachers and education administrators was obtained by stratified sampling technique. The instruments used for data collection included semi-structured interviews form, Likert's scale questionnaires, and records of focus group discussions. The statistics used for data analysis were descriptive statistics, and Exploratory Factor Analysis as well as content analysis was used. The research findings revealed that: (1) the development of Cooperative and Work-Integrated Education in higher vocational art design in Henan Province consisted of 5 components: teaching quality management; organization management; college and enterprise development management; leadership management; social services management; and (2) there were 11 guidelines for development of Cooperative and Work-Integrated Education in Henan Higher Vocational Colleges, which were as follows: three guidelines on strengthening teaching quality management, two guidelines on strengthening organization management, two guidelines on promoting college-enterprise cooperation development management, two guidelines on strengthening leadership management, and two guidelines on improving the level of social services.